Strategi Aksesibilitas Layanan Inklusi Di Perpustakaan Universitas Islam Negeri Sunan Kalijaga Selama Study from home (SfH) - Susiana Rahayu; Roro Isyawati Permata Ganggi (Jurnal Ilmu Perpustakaan, 2024)
This article focuses on the inclusion services strategy for students with disabilities in libraries. This study aimed to determine how the strategy of library inclusion services at the Sunan Kalijaga State Islamic University Library during study at home was implemented (SfH). Data were collected observation, semi-structured interviews, and documentation with librarians, coordinator of the information technology service sector, and students with disabilities. The results indicate that the Sunan Kalijaga State Islamic University Library has implemented an inclusive service strategy in order to serve students with has implemented technology, such as online user education, social media integration, and official library numbers. Even though technology has been incorporated, the employed strategies are not optimal. Libraries must collaborate with diverse parties to maximize the strategy services and implementation services they already have. Periodically evaluating the inclusion services to determine if they are still effective is necessary to maximize the inclusion services.